Tolerant and Moderate Islamic Religious Practices in Pesantren Al-Qodir - Miftahuddin, Miftahuddin (el Harakah: Jurnal Budaya Islam, 2023)
Creating peace and harmony among communities is an Islamic teaching must be implemented to achieve goodness and harmony among humanity. It is what K.H. Masrur Ahmad MZ and his pesantren are currently doing, not only in theory but also in practice. This article aims to explain the practice of a tolerant and moderate interpretation of Islam, or often referred to as "Islam rahmatan li al-alamin," which is led by K.H. Masrur as the caretaker of Pesantren Al-Qodir. This research uses a qualitative method with a symbolic interaction approach. Data collection is carried out through in-depth interviews and observations, and relevant documentation is gathered. The results show that, by not eliminating the basic principles and values of Islam, the Islamic religiosity practiced in pesantren, Al-Qodir, is Islam that is able to sustain dialogue with various groups, other religions, cultures, and local communities. In this context, K.H. Masrur goes beyond the interpretation of a tolerant and moderate understanding of Islam, and also demonstrates how tolerance is implemented in real actions, such as inviting Christians to participate in the sacrifice of animals for Qurban, staging local art festivals, and other initiatives. Menciptakan perdamaian dan kebersamaan di kalangan masyarakat adalah ajaran Islam yang harus diimplementasikan agar tercipata kebaikan dan keharmonisan di antara umat manusia. Hal inilah yang sedang dilakukan K.H. Masrur Ahmad MZ dan pesantrennya, yang tidak hanya dalam tataran pemikiran atau teori tetapi juga praktik. Artikel ini bertujuan menjelaskan praktik keberagamaan Islam toleran dan moderat atau sering disebut Islam rahmatan li al-alamin yang dimotori oleh K.H. Masrur sebagai pengasuh pesantren Al-Qodir. Penelitian ini menggunakan metode kualitatif dengan pendekatan interaksi simbolik. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa dengan tidak menghilangkan prinsip-prinsip dasar dan nilai-nilai Islam, keberagamaan Islam di pesantren Al-Qodir adalah Islam yang mampu berdialog dengan berbagai kelompok, agama lain, budaya, dan masyarakat lokal. Dalam konteks ini, K.H. Masrur tidak berhenti dalam hasil penafsiran ajaran Islam yang toleran dan moderat, akan tetapi bagaimana praktik toleransi diimplementasikan dalam tindakan yang nyata, seperti mengundang kaum nasrani ikut dalam penyembelihan hewan kurban, pagelaran vestifal kesenian lokal, dan lainnya.